Biochar in the management of nitrogen and phosphorus to produce angico seedlings - Lima, Stefany Lorrayny; Marimon Junior, Ben Hur; Melo-Santos, Kelyane da Silva; Reis, Simone Matias; Petter, Fabiano André; Vilar, Cesar Crispim; Marimon, Beatriz Schwantes (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of biochar applied together with the macronutrients N and P, for the formation of substrate, on the growing of angico (Anadenanthera colubrina) seedlings for forest restoration. The experiments were conducted in a forest nursery, in a completely randomized block design. Interactions were studied between increasing concentrations of biochar and of N as urea, and between concentrations of biochar and P as superphosphate, added to a Yellow Oxisol. Seedling patterns of growth, quality, and nutrition were determined, and the results were subjected to the study of polynomial regression (response surface). The interaction between biochar and N favored leaf nutrition and leaf‑concentration of Mg of angico seedlings; however, it did not influence plant growth. Angico seedlings subjected to the application of biochar and P showed higher nutrition and nutrient use efficiency of Ca and K. Biochar application with N and P to the substrate shows potential for the production of quality seedlings, which favors the success of practices for forest restoration in regions with low soil fertility and subjected to water stress periods.
Keywords: Anadenanthera colubrina; reforestation; substrate; superphosphate; urea